High prevalence of IncP‐1 plasmids and IS1071 insertion sequences in on‐farm biopurification systems and other pesticide‐polluted environments. Issue 3 (24th July 2013) - Dunon, Vincent; Sniegowski, Kristel; Bers, Karolien; Lavigne, Rob; Smalla, Kornelia; Springael, Dirk
Abstract: Mobile genetic elements (MGEs) are considered as key players in the adaptation of bacteria to degrade organic xenobiotic recalcitrant compounds such as pesticides. We examined the prevalence and abundance of IncP‐1 plasmids and IS 1071, two MGEs that are frequently linked with organic xenobiotic degradation, in laboratory and field ecosystems with and without pesticide pollution history. The ecosystems included on‐farm biopurification systems (BPS) processing pesticide‐contaminated wastewater and soil. Comparison of IncP‐1/IS 1071 prevalence between pesticide‐treated and nontreated soil and BPS microcosms suggested that both IncP‐1 and IS 1071 proliferated as a response to pesticide treatment. The increased prevalence of IncP‐1 plasmids and IS 1071 ‐specific sequences in treated systems was accompanied by an increase in the capacity to mineralize the applied pesticides. Both elements were also encountered in high abundance in field BPS ecosystems that were in operation at farmyards and that showed the capacity to degrade/mineralize a wide range of chlorinated aromatics and pesticides. In contrast, IS 1071 and especially IncP‐1, MGE were less abundant in field ecosystems without pesticide history although some of them still showed a high IS 1071 abundance. Our data suggest that MGE‐containing organisms were enriched in pesticide‐contaminated environments like BPS where they might contribute to spreading of catabolic genes and to pathway assembly.